Організаційно-правові засади формування та функціонування персоналу установ виконання покарання - Галай, Андрій Олександрович; Galay, A. O. (My University, 2003)
АНОТАЦІЇ Галай А.О. Організаційно-правові засади формування та функціонування персоналу установ виконання покарання. — Рукопис. Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.07 — теорія управління; адміністративне право і процес; фінансове право; інформаційне право. Національна академія державної податкової служби України. — Ірпінь, 2004. Дисертація присвячена комплексному дослідженню організаційно-правових засад формування та функціонування персоналу установ виконання покарання. У роботі досліджується стан наукової розробки проблеми, дається характеристика наукових джерел та нормативно-правового регулювання. Автор обґрунтовує та формулює поняття персоналу установ виконання покарання, розкриває наукові положення щодо персоналу установ виконання покарання та його діяльності як об’єкта правового дослідження. Змодельовані системи вимог до персоналу установ виконання покарання, організації підготовки та управління підбором персоналу. На основі аналізу теоретичних засад організації та управління персоналу установ виконання покарання, проведеної класифікації персоналу за функціями, які він виконує, автор визначає шляхи функціонального забезпечення діяльності персоналу установ виконання покарання. Ключові слова: персонал установ виконання покарання, підбір персоналу установ виконання покарання, підготовка персоналу установ виконання покарання, функціонування персоналу установ виконання покарання, класифікація персоналу установ виконання покарання, цілі та завдання діяльності персоналу установ виконання покарання, система вимог до персоналу установ виконання покарання Andrew O. Galay. Organizationally legal bases of formation and functioning of the personnel of establishments of execution of punishment. — Manuscript. The dissertation on competition of a scientific degree of the candidate of juridical sciences on a specialty 12.00.07 — the theory of management; administrative law and process; the financial law; the information law. National academy of State Tax Service of Ukraine. — Irpin, 2004. The dissertation is devoted to complex research of organizationally legal bases of formation and functioning of the personnel of establishments of execution of punishment. In the work state of scientific development of a the problem is investigated, the characteristic of scientific sources and normatively-legal regulation is given. The author proves and formulates concept of the personnel of establishments of execution of punishment, opens scientific position to the personnel of establishments of execution of punishment and its activity as object of legal research. The modeled systems of requirements to the personnel of establishments of execution of punishment, the organization of preparation management of selection of personnel. Proceeding from analysis of theoretical bases of the organization and management of the personnel of establishments of execution of punishment, the author carries out classification by the personnel behind the functions executed by them, the author defines ways of functional maintenance of activity the personnel of establishments of execution of punishment. Key words: the personnel of establishments of execution of punishment, selection the personnel of establishments of execution of punishment, preparation of the personnel of establishments of execution of punishment, functioning of the personnel of establishments of execution of punishment, classification of the personnel of establishments of execution of punishment, the purpose and the task of activity the personnel of establishments of execution of punishment, system of requirements of the personnel of establishments of execution of punishment.
Organizationally legal bases of formation and functioning of the personnel of establishments of execution of punishment
Keywords: персонал установ виконання покарання; ір персоналу установ виконання покарання; підготовка персоналу установ виконання покарання; функціонування персоналу установ виконання покарання; класифікація персоналу установ виконання покарання; цілі та завдання діяльності персоналу установ виконання покарання; система вимог до персоналу установ виконання покарання; personnel of establishments of execution of punishment; selection the personnel of establishments of execution of punishment; preparation of the personnel of establishments of execution of punishment; functioning of the personnel of establishments of execution of punishment; classification of the personnel of establishments of execution of punishment; purpose and the task of activity the personnel of establishments of execution of punishment; system of requirements of the personnel of establishments of execution of punishment